2016
DOI: 10.1177/1756283x15621229
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: third-line susceptibility-guided treatment for Helicobacter pylori infection

Abstract: Background: Susceptibility-guided therapies (SGTs) have been proposed as preferable to empirical rescue treatments after two treatment failures. The aim of this study was to perform a systematic review and meta-analysis evaluating the effectiveness and efficacy of SGT as third-line therapy. Methods: A systematic search was performed in multiple databases. Studies reporting cure rates of Helicobacter pylori with SGT in third-line therapy were selected. A qualitative analysis describing the current evidence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 45 publications
(67 reference statements)
1
51
0
Order By: Relevance
“…In the absence of a national registry other regional centres in the United States could consider a similar review of their available data to provide comparisons across regions, in order to help facilitate antibiotic therapy for refractory HP. Routine culture has so far not been recommended, as it is not clearly beneficial over empirical rescue therapy . Even in our study, given that culture rate was approximately 70%, many patients would undergo an endoscopy without subsequent culture results, and culture is certainly an imperfect test.…”
Section: Discussionmentioning
confidence: 65%
“…In the absence of a national registry other regional centres in the United States could consider a similar review of their available data to provide comparisons across regions, in order to help facilitate antibiotic therapy for refractory HP. Routine culture has so far not been recommended, as it is not clearly beneficial over empirical rescue therapy . Even in our study, given that culture rate was approximately 70%, many patients would undergo an endoscopy without subsequent culture results, and culture is certainly an imperfect test.…”
Section: Discussionmentioning
confidence: 65%
“…However, microbiologic culture is not available in many centers and is rarely undertaken in clinical practice. Additionally, a recent review revealed no clear benefit of third‐line susceptibility‐guided treatment . Collectively, these findings question the utility of culture in this context …”
Section: Discussionmentioning
confidence: 99%
“…The eradication rates of susceptibility-guided treatments are generally higher than those of empirical treatment regimens[7,81,86]. Recent studies have also shown that susceptibility-based treatment improves the efficacy of the therapy used after first- or second-line treatment failure as well as the efficacy of first-line therapy (Tables 1 and 2)[26,73,82-84,87-92].…”
Section: Contribution Of Antimicrobial Susceptibility Testing To the mentioning
confidence: 99%